Multiple pathways guide oxygen diffusion into flavoenzyme active sites - Riccardo Baron (2018)
Dioxygen (O2) and other gas molecules have a fundamental role in a variety of enzymatic reactions. However, it is only poorly understood which O2 uptake mechanism enzymes employ to promote efficient catalysis and how general this is. We investigated O2 diffusion pathways into monooxygenase and oxidase flavoenzymes, using an integrated computational and experimental approach. Enhanced-statistics molecular dynamics simulations reveal spontaneous protein-guided O2 diffusion from the bulk solvent to preorganized protein cavities. The predicted protein-guided diffusion paths and the importance of key cavity residues for oxygen diffusion were verified by combining site-directed mutagenesis, rapid kinetics experiments, and high-resolution X-ray structures. This study indicates that monooxygenase and oxidase flavoenzymes employ multiple funnel-shaped diffusion pathways to absorb O2 from the solvent and direct it to the reacting C4a atom of the flavin cofactor. The difference in O2 reactivity among dehydrogenases, monooxygenases, and oxidases ultimately resides in the fine modulation of the local environment embedding the reactive locus of the flavin.